PENGEMBANGAN SUMBER DAYA MANUSIA PADA DINAS TENAGA KERJA DAN TRANSMIGRASI PROVINSI SULAWESI TENGAH - Nunung Kurniah Wijaya; Syaharuddin Hattab; Dandan Haryono (JURNAL ILMIAH RESEARCH STUDENT, 2024)
The aim of this research is to analyze the implementation of human resource development carried out by the Central Sulawesi Province Manpower and Transmigration Office. The type of research currently being carried out is descriptive research with a qualitative approach. Informants in this study were determined using a purposive technique with a total of 7 informants. This research uses qualitative data, while the data sources in this research are primary data obtained from observations and interviews, as well as secondary data. Analyzing data uses James Spradley's thinking which is known as a gradual forward flow, divided into four types, namely making domain analysis, making taxonomic analysis, making component analysis, and finding cultural themes. The results of the research show that the implementation of HR development for the Manpower and Transmigration Department of Central Sulawesi Province has been carried out but has not run optimally, this is because development through learning activities has been carried out but has not been effective. Because encouragement to direct employees to be motivated to learn independently is still rarely carried out by the Central Sulawesi Province Manpower and Transmigration Office, so it still needs to be improved. Apart from that, development through edication (education) activities has also been implemented but has not been effective because there are still many employees with civil servant status who currently still have secondary education and are not yet motivated to take part in development programs through study assignments. Meanwhile, the other two aspects, namely training, have been carried out and the implementation is going well, where the agency always assigns its employees to every training activity and seminar held by competent institutions at both regional and central levels. Then the development aspect has also been carried out and the implementation has gone well, namely developing employee competency through mentoring activities, employee involvement in special or strategic programs, and giving additional tasks has been carried out quite well by the Central Sulawesi Province Manpower and Transmigration Office.